The correlation between environmental, social and governance ratings and the transparency in Johannesburg Stock Exchange companies’ tax practices - Cara Thiart (South African Journal of Economic and Management Sciences, 2023)
Background and aim: The study explores the correlation between environmental, social and governance (ESG) ratings and the extent of corporate tax transparency to investigate whether ESG ratings are indicative of transparent corporate tax practices. To gain more insight, the correlation exploration is extended to the ratings achieved in the governance category and the transparency and reporting subcategory included in the overall ESG rating.